Scots pine (Pinus sylvestris L.) in natural and cultural populations of Central Kazakhstan: A literature review - Tuleshova , K.; Kali , A.; Silantyeva , M. (Fundamental and Experimental Biology, 2025)
This review summarizes recent findings on the morphological, anatomical, and biochemical characteristics of Pinus sylvestris L. in both natural and cultural established populations in Central Kazakhstan. Natural populations, occurring in the mountainous zones of the Kazakh Uplands, are characterized by ecological stability, climatic resilience, and high genetic diversity. In contrast, cultural plantations, established to mitigate desertification and stabilize soils, exhibit altered morphometric traits and a decrease in biodiversity due to monocultural practices. Comparative analysis of recent CIS and Kazakhstani studies reveals that environmental stressors, including technogenic pollution and soil degradation, significantly affect anatomical parameters of needles, radial growth, and phytochemical composition. The accumulation of heavy metals, decline in photosynthetic pigments, and variation in essential oil profiles reflect adaptive responses of P. sylvestris to anthropogenic impacts. The observed differences between natural and cultural populations underscore the need for region-specific forest management strategies, informed by anatomical and biochemical diagnostics. These findings support the development of improved selection and breeding programs tailored to Kazakhstan’s diverse ecological zones.